Libya : Staff Report For The 2013 Article Iv Consultation. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2013)
The political and security environment remains uncertain in Libya. Libya faces the challenges of stabilizing the economy and responding to the aspirations of the revolution. The near-term outlook is favorable, but there are significant risks. The overarching policy objective should be to foster inclusive growth. Banks are not intermediating, and resources should be devoted to its effective implementation. Expenditure is skewed toward wages and subsidies. Libya needs to adopt a comprehensive reform strategy. The government agrees with the assessment of the economic outlook and associated risks and policy options as outlined by Executive Directors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet